PENINGKATAN KECERDASAN EKOLOGIS SISWA MENGENAI PELESTARIAN AIR MELALUI PEMBELAJARAN IPS BERBASIS NILAI-NILAI KEARIFAN LOKAL SITU SANGIANG (Penelitian Tindakan Kelas di Kelas IV SDN Sukaperna I Majalengka) - Nugraha, Febby Fajar Fajar (JURNAL PENDIDIKAN ILMU SOSIAL, 2016)
This research is motivated by a decrease in the level of quality of life in line with the decline in volume and quality of water that is in the earth, with the aim to improve the ecological intelligence students about water conservation. This classroom action research conducted with fourth grade students at SDN Sukaperna I Majalengka. Solution action used is to apply learning-based IPS values of local wisdom situ sangiang so focused for students to interact with the natural surroundings. This research was conducted in three cycles consisting of a cycle component of knowledge, awareness and application. The results showed that the application of the values of local wisdom in learning IPS can increase the intelligence of the ecological aspects of water conservation. It is evident from the percentage component of intelligence character formation of ecological aspects of water conservation in the form of knowledge, awareness, and applications continue to increase at every meeting in the cycle. Thus, the hypothesis has been made evident that the application of the values of local wisdom can increase the intelligence of the students on the ecological aspects of water conservation in social studies learning.Keywords: Intelligence ecological, water conservation, local wisdom, social studies learning.